KAJIAN TEKNIS PETA JALAN PERALATAN OPERASIONAL METEOROLOGI DIGITAL DI BADAN METEOROLOGI, KLIMATOLOGI, DAN GEOFISIKA - Maulana Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The shift from conventional to digital weather observation systems has become a key priority for Indonesia’s Meteorology, Climatology, and Geophysics Agency (BMKG) in order to improve data accuracy. This research focuses on creating a roadmap for Digital Meteorological Operational Equipment by identifying both minimum and ideal requirements and assessing equipment performance based on international benchmarks, particularly those set by the World Meteorological Organization (WMO). Using a descriptive quantitative approach, the study involves data collection, technical evaluation, and the formulation of the roadmap. Findings show that while the minimum standards have been met, fulfilling the ideal standards would require the addition of 42 more units of Digital Meteorological Operational Equipment. Based on the 2024 Service Level Agreement (SLA), the equipment has achieved an average uptime of 98–100%, supported by regular maintenance and calibration to ensure the equipment's operational reliability. The resulting roadmap offers strategic direction for future equipment procurement, aiming to enhance the quality of meteorological services to align with both national and international standards. This research is intended to serve as a reference for managing digital meteorological tools to ensure the delivery of precise and dependable weather data.